The role and impact of social media on Arab networks on Arab Spring: a case study on the Egyptian Revolution - Allam, Mai Nabil (AUC Knowledge Fountain, 2012)
The wide spread of social media allows undisciplined groups to share and communicate quickly at a reduced cost so that they can easily form collective actions. Thus, electronic revolutions begin worldwide as all people for the first time in history are politically conscious and interactive. This study examines the role of social media in the Arab uprising with the Egyptian revolution as a case study. This primary research linked both the uses and gratification theory to the new usage of social media and the spiral of silence theory to people confidence in forming collective actions. A survey was conducted among a purposive sample of Egyptians (353 participants) to examine role of social networking websites in the Egyptian revolution and relationship between using these websites and political participation. An in depth interviews were conducted with nine media experts and political activists regarding role that social networking websites played in the Egyptian revolution. The findings support the spiral of silence theory whereby people are encouraged to go to the street and demonstrate when they know through the social networking websites that they hold the majority opinions and that most of the Egyptians are against Mubarak's regime. Experts opinions support the survey findings that social networking websites have a crucial role in the Egyptian revolution in motivating the protesters and facilitating communication but there are many causes that pushed Egyptians to demonstrate such as poverty, oppression, and corruption. Without the protesters' blood and persistence, the revolution would have never succeed.